2018
DOI: 10.1111/jgh.14520
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the programmed death‐ligand 1 gene is associated with its protein expression and prognosis in gastric cancer

Abstract: Background and Aim While the incidence and mortality of gastric cancer (GC) remains high, and prognosis of GC remains poor, molecules in programmed death‐1 (PD‐1), programmed death‐ligand 1 (PD‐L1), and programmed death‐ligand 2 (PD‐L2) pathway are promising prognostic biomarker of GC. The polymorphisms on PD‐1, PD‐L1, and PD‐L2 may be associated with their protein expressions and affect the survival of GC patient. Methods Seven hundred fifty‐six GC patients who voluntarily supplied blood samples were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…It has been proposed that gene expression could be potentially affected by genetic polymorphisms [21,61,62,63]. Alterations in the expression of PD-1 and PDL-1 were detected in many cancer types including gastric cancer, lung cancer, thyroid cancer, laryngeal carcinoma, extrapulmonary small cell carcinoma, and breast cancer [63,64,65,66,67,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that gene expression could be potentially affected by genetic polymorphisms [21,61,62,63]. Alterations in the expression of PD-1 and PDL-1 were detected in many cancer types including gastric cancer, lung cancer, thyroid cancer, laryngeal carcinoma, extrapulmonary small cell carcinoma, and breast cancer [63,64,65,66,67,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Kogure and Kataoka (59) also reported that structural variants induce PD-L1 overexpression in ATL. More recently, a study in gastric cancer has revealed that PD-L1 rs2297136 AA+AG genotype, a new polymorphism in 3′-UTR of PD-L1 , is also correlated with the positive protein expression of PD-L1 (60).…”
Section: Pd-l1 Regulation In Cancermentioning
confidence: 99%
“…Emerging clinical data have shown that the upregulation of PD-L1 in multiple tumor types has prognostic implication and can predict the clinical response to PD-1 blockade therapy. 12,13 Although the potential clinical relevance of PD-L1 expression in ICC has already been reported in several previous studies, the prognostic value of PD-L1 for ICC is still controversial. [14][15][16][17] This study aimed to examine the clinicopathological and prognostic roles of T-lymphocyte-based IS, following similar principles described by Galon et al in ICC.…”
Section: Introductionmentioning
confidence: 99%